Determinants of physical activity participation among the Universiti Putra Malaysia students - Kay, Thwe; Hayati, K. S.; Minhat, H. S. (Community Health Society Malaysia, 2016)
Background: The prevalence of non-communicable diseases in Malaysia are still rising, despite a slight increase in the prevalence of physical activity from 64.8% to 66.5% according to National Health and Morbidity Surveys 2011 and 2015. This rising trend is mostly related to environmental, socio-economic changes in relation to the development of a country. Determining the gap and improving the environmental health policy and strategy would be helpful for the community. Materials and Methods: A cross-sectional study was conducted in the Universiti Putra Malaysia from September 2015 to May 2016.The sample size was calculated by using two-proportion formula and the proportionate stratified sampling method was used in this study. The short version of International Physical Activity Questionnaire (IPAQ) was used for physical activity measurement and the Physical and Social Environmental Scales (PASES) was used to measure the physical and social environmental factors. Result: The prevalence of physical activity participation in this study was 72.2%. The majority of the respondents were below 24 years of age (61. 4%), female (63.8%) and Malay (75.1%). The female respondents were less likely to participate in physical activity than male (p= 0.01) (OR= 0.558; CI: 0.358-0.869). The respondents who agreed to have poor neighbourhood safety (p=0.034) (OR=0.623; CI: 0.403-0.965) and good social cohesion (p=0.005) (OR= 1.956; CI: 1.23 - 3.11) were more physically active. Conclusion: The predictors of physical activity participation were female, the neighbourhood safety, and social cohesion.